2019
DOI: 10.1016/j.drugpo.2018.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ and clinicians’ perspectives of co-use of cannabis and opioids for chronic non-cancer pain management in primary care

Abstract: Background: The prevalence of opioid-associated morbidity and mortality underscores the need for research on non-opioid treatments for chronic non-cancer pain (CNCP). Pain is the most common medical condition for which patients request medical cannabis. Limited research indicates that patients are interested in cannabis as a potential addition to or replacement for opioid medication. This analysis reports on CNCP patient and clinician perceptions about the co-use of cannabis and opioids for CNCP management. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 38 publications
2
40
0
Order By: Relevance
“…Studies already report concomitant use of recreational cannabis and opioids among people with chronic noncancer pain. 15 , 20 A four-year prospective observational study found cannabis users had greater pain and lower self-efficacy in managing pain, and there was no evidence it reduced pain severity or interference or exerted an opioid-sparing effect. 15 There is therefore an urgent need to address politician and public misconceptions about cannabinoids and preventive action to limit the same aggressive marketing approaches for medicinal cannabinoids that enabled the opioid epidemic; a new prescribing epidemic may be imminent.…”
Section: Many Patients With Low Back Pain Are Still Receiving the mentioning
confidence: 99%
“…Studies already report concomitant use of recreational cannabis and opioids among people with chronic noncancer pain. 15 , 20 A four-year prospective observational study found cannabis users had greater pain and lower self-efficacy in managing pain, and there was no evidence it reduced pain severity or interference or exerted an opioid-sparing effect. 15 There is therefore an urgent need to address politician and public misconceptions about cannabinoids and preventive action to limit the same aggressive marketing approaches for medicinal cannabinoids that enabled the opioid epidemic; a new prescribing epidemic may be imminent.…”
Section: Many Patients With Low Back Pain Are Still Receiving the mentioning
confidence: 99%
“…Indeed, few data, other than anecdotal reports, are available supporting the use of marijuana for cLBP, and concerns within the medical community over toxicity and abuse remain high. 25 , 26 On the other hand, currently, most states in the US have medical marijuana laws, and many states now permit recreational use. Formal study of the utility of marijuana for pain might help to address this disparity of opinions and foster more constructive conversations between patients and their medical providers.…”
Section: Discussionmentioning
confidence: 99%
“…Opioids have been used for many years in clinical practice, especially for cancer pain management, anaesthesia, and postoperative analgesia [20,21]. Studies on the side effects of opioids have mainly focused on nausea, vomiting, postoperative delirium, and breathing effects, and the effects of opioids on monocyte-endothelial adherence are unknown [22].…”
Section: Discussionmentioning
confidence: 99%